Dukungan Keluarga terhadap Kesepian pada Lansia - Muhammad Khidri Alwi; Ramli, Rahmawati; Andi Zaenab Nganro; Alam, Rizqy Iftitah (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2024)
Loneliness is a problem experienced by a person, which is unpleasant and absorbs in the form of sadness, helplessness, hopelessness and emptiness. This condition is where people feel left out of their group and are not cared about by the people around them. Family support is the most important part in helping elderly people solve all the problems they face. If there is a relationship from the family, self-confidence will increase and motivation to face problems that occur will increase. Family support is a factor that influences the well-being of the elderly. This study aims to determine the relationship between family support and loneliness in the elderly. The research used is quantitative research with a research design using a cross sectional study. The sampling technique used was Purposive Sampling with a sample size of 64 samples. The data analysis carried out in this research was bivariate analysis. The relationship test was carried out using the Chi Square statistical test with a significance level of <0.05. The results of this study show that there is insufficient family support for 50 (78%) elderly people, while there is good family support for 14 (22%) elderly people. Loneliness in the elderly who are included in the unequal category is 12 (19%) elderly, while those who are included in the equal category are 52 (81%) elderly. There is a significant relationship between family support for loneliness in the elderly in the working area of ​​the Bontoimarannu Community Health Center, Gowa Regency and p value = 0.00 (p < 0.05. The conclusion of this research is that more than half of the elderly have less family support, most of the elderly experience equality in the Bontomarannu Community Health Center area, Gowa Regency. There is a relationship between family support and loneliness among the elderly in the region Bontomarannu Community Health Center, Gowa Regency.